Immigrants and Firms' Productivity: Evidence from France - Cristina Mitaritonna; Gianluca Orefice; Giovanni Peri (Institute for the Study of Labor (IZA), 2014)
Immigrants may complement native workers, increase productivity, allow specialization by skill in the firm and lower costs. These effects could be beneficial for the firm and increase its productivity and profits. However not all firms use immigrants. Allowing firms to have differential fixed cost in hiring immigrants we analyze the impact of an increase in local supply of immigrants on firms' immigrant employment and firm's productivity. Using micro-level data on French firms, we show that a supply-driven increase in foreign born workers in a department (location) increases the productivity of firms in that department. We also find that this effect is significantly stronger for firms with initially zero level of foreign employment. Those are also the firms whose share of immigrants increases the most. We also find that the positive productivity effect of immigrants is associated with faster growth of capital and improved export performances of the firms. Finally we find a positive effect of immigration on wages of natives and on specialization of natives in complex occupations, that is common to all firms in the department.
Keywords: F22; E25; J61; 330; immigrants; firms; productivity; heterogeneity; fixed costs of hiring